The Effect Of Red Betel Leaf Ethanol Extract (Piper Crocatum) To Histopathological Image Of Rat (Rattus Norvegicus) Pancreas Induced By Alloxan - Jose Mario Leonardo Vivaldy (Universitas Nusa Cendana, 2025)
Introduction: Red betel leaf has secondary metabolite compounds, namely flavonoids, alkaloids, saponins and tannins. Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to decreased insulin secretion, impaired insulin action, or both which produce Reactive Oxygen Species (ROS). Red betel leaf extract is expected to reduce damage to the pancreas by inhibiting the formation of ROS by the antioxidants contained therein. Method: This research is a laboratory experimental study with a true experimental design posttest only with a control group approach. The sample was divided into 5 groups, where each group consisted of 6 rats. Necrosis and degeneration were assessed in pancreas preparations. The data were analyzed by the Kruskal-Wallis test and followed by the Post Hoc LSD test. Results: The Kruskall-Wallis test found a significant difference between administration of red betel leaf extract and histopathological features of the pancreas of necrosis rats with p = 0.000 and degeneration with p = 0.001 (p<0.05). Discussion: The administration of red betel leaf extract proved to have positive effect on improving pancreas histopathology in alloxan-induced rats. Conclusion: There was a significant difference between the histopathological features of rat pancreas (Rattus norvegicus) after being given red betel leaf extract (Piper crocatum).